A GBS-based genome-wide association study reveals the genetic basis of salinity tolerance at the seedling stage in bread wheat (Triticum aestivum L.) - Akram, Saba; Ghaffar, Maria; Wadood, Ayesha; Shokat, Sajid; Hameed, Amjad; Waheed, Muhammad Qandeel; Arif, Mian Abdur Rehman (Frontiers in Genetics, 2022)
A total of 20% cultivated area and 9-34% of irrigated agricultural land of world is affected due to high salinity which ultimately leads to yield losses in crops. In current study we have evaluated seven salt tolerance related traits at seedling stage in a set of 138 pre-breeding lines (PBLs) and identified 63 highly significant marker trait associations (MTAs) linked to salt tolerance. Different candidate genes were identified using the In silico analysis where many were involved in various stress conditions in plants, including glycine-rich cell wall structural protein 1-like, metacaspase-1, glyceraldehyde-3-phosphate dehydrogenase GAPA1 and plastidial GAPA1. Some of these were structural protein and participate in cell wall structure, some were linked to programmed cell death and reported to have abiotic stress responsive role in wheat and other plants. In addition, using the MGIDI (Multi-Trait Genotype-Ideotype Distance Index) protocol, the best performing lines under salt stress were identified. The SNPs spotted in this study and the genotypes with favorable alleles provide an excellent source to impart salt tolerance in wheat.